Case reportRescue percutaneous coronary recanalization of right coronary artery by retrograde approach - Bryniarski, Leszek; Kameczura, Tomasz; Surowiec, Sławomir; Dudek, Dariusz; Czarnecka, Danuta (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
We describe the case of a 62-year-old female patient in whom there was an occlusion of collaterals and acute inferior wall ischemia during the opening procedure of right coronary artery (RCA) chronic total occlusion. Rescue percutaneous coronary intervention (PCI) of RCA by the retrograde approach was performed preventing heart muscle damage. In this article we discuss the issue of PCI by the retrograde technique.